Pengembangan Media Pembelajaran Digital Berbasis Augmented Reality Pada Topik Klasifikasi Hewan Berdasarkan Habitatnya - Nurhasanah, Yeni; Putri, Daniah Adjani (MULTINETICS, 2020)
Augmented Reality as one of the developing fields in the Industrial Age 4.0 has been widely used in various fields. Augmented Reality (AR) can be used to deliver the  information that may be very difficult to do directly in the real world. Many fields use augmented reality based media to deliver the information to their target users. Augmented Reality has been developed to help the learning process become more fun and interactive. The learning process aims to provide experience and share information and knowledge in an interesting and meaningful way for students. The process that was previously impossible for students can be helped by using augmented reality-based learning media. One of them is in learning science in elementary schools on the topic of animal recognition based on their habitat. Through this digital learning media based on augmented reality, students can see how the physical shape of the animals in question is 3D by using an Android device. Augmented Reality-based digital learning media created using Unity 3D and Vuforia. This application is capable of displaying 3D models also able to present a video explanation of the 3D model. In this project virtual buttons are also applied so that users are more challenged in using it.